Investasi hijau: mengintergrasikan faktor enviromental, social dan governance dalam keputusan investasi - Pandu Adi Cakranegara (Penerbit Goodwood, 2021)
Purpose: This research tries to integrate ESG factors in investment decision making in Indonesia. Research methodology: This research is applied research in which an existing framework is applied to a new environment. This study shows that the ESG factor can be applied in making investment decisions in Indonesia. It requires integration using multiple sources because companies in Indonesia are still not required to provide full disclosure regarding ESG factors. Results: The two industries in this study, namely the agriculture and mining industries, have similarities and both of them can benefit from applying social values ??to their business operations. When a company has a social impact, the community will support its existence because without the company, their socio-economic activities will be disrupted. Thus, it will be in the interest of the community and parties dealing with the company to maintain the company's existence. In the end, the conflict of interest will disappear and goal congruence will arise. When this condition is achieved, the company will be able to operate more optimally and increase its value. Limitations: This research limited to Indonesia context especially the agricultural and mining industry and their social context. Contribution: This research contributes on applying Porter Framework together with Responsible investment. Keywords: Porter, Responsible investment, Social economy, Government